A comprehensive assessment of memory, delay aversion, timing, inhibition, decision making and variability in attention deficit hyperactivity disorder: advancing beyond the three-pathway models. Issue 9 (July 2014) - Coghill, D. R.; Seth, S.; Matthews, K.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Although attention deficit hyperactivity disorder (ADHD) has been associated with a broad range of deficits across various neuropsychological domains, most studies have assessed only a narrow range of neuropsychological functions. Direct cross-domain comparisons are rare, with almost all studies restricted to less than four domains. Therefore, the relationships between these various domains remain undefined. In addition, almost all studies included previously medicated participants, limiting the conclusions that can be drawn. We present the first study to compare a large cohort of medication-naive boys with ADHD with healthy controls on a broad battery of neuropsychological tasks, assessing six key domains of neuropsychological functioning. Method The neuropsychological functioning of 83 medication-naive boys with well-characterized ADHD (mean age 8.9 years) was compared with that of 66 typically developing (TYP) boys (mean age 9.0 years) on a broad battery of validated neuropsychological tasks. Results Data reduction using complementary factor analysis (CFA) confirmed six distinct neuropsychological domains: working memory, inhibition, delay aversion, decision making, timing and response variability. Boys with ADHD performed less well across all six domains although, for each domain, only a minority of boys with ADHD had a deficit [effect size (% with deficit) ADHD versus TYP: working memory 0.95 (30.1), inhibition 0.61 (22.9), delay aversion 0.82 (36.1), decision making 0.55 (20.5), timing 0.71 (31.3), response variability 0.37 (18.1)]. Conclusions The clinical syndrome of ADHD is neuropsychologically heterogeneous. These data highlight the complexity of the relationships between the different neuropsychological profiles associated with ADHD and the clinical symptoms and functional impairment.